Relation between muscle mass, motor units and type of training in master athletes. (24th October 2014) - Drey, Michael; Sieber, Cornel C.; Degens, Hans; McPhee, Jamie; Korhonen, Marko T.; Müller, Klaus; Ganse, Bergita; Rittweger, Jörn
Summary: Objective: The aim of this study was to measure the number of motor units and muscle mass in power‐trained and endurance‐trained master athletes compared with community‐dwelling older adults. Methods: Seventy‐five master athletes (52 power‐ and 23 endurance‐trained athletes) were recruited at the 2012 European Veteran Athletics Championships in Zittau (Germany). One hundred and forty‐nine community‐dwelling older adults served as controls. In all participants, the motor unit number index (MUNIX) in the hypothenar muscle and whole body muscle mass was determined by bioelectrical impedance analysis (BIA). Results: In both male and female master athletes, there were significant negative correlations between age and muscle mass (female: r = −0·510, P = 0·002; male: r = −0·714, P <0·001). Master athletes showed a weak correlation ( r = −0·295, P = 0·010) between MUNIX and age. Master athletes exhibited significantly higher values than the control group with regard to both muscle mass ( P = 0·002) and motor units ( P = 0·004). Subanalysis showed that only power trained master athletes had both a larger muscle mass ( P <0·001) and a higher MUNIX ( P = 0·014) than the control group. Among the master athletes, power‐trained athletes had a larger ( P <0·001) muscle mass than endurance‐trained athletes. Conclusions: The present data of master athletes are compatible with the hypothesis of an age‐related decline in whole body muscle mass and motor units. Nevertheless, the data suggest that the master athletes' high level of physical activity may protect motoneurons. In addition, power training seems to have a positive effect on muscle mass and could therefore be an effective method of training to prevent sarcopenia.